Age-Related Trends in the Treatment and Outcomes of Ruptured Cerebral Aneurysms: A Study of the Nationwide Inpatient Sample 2001–2009 - Brinjikji, W. (AJNR Am J Neuroradiol, 2013)
BACKGROUND AND PURPOSE: Patient age substantially influences treatment decisions for ruptured cerebral aneurysms. It would be useful to understand national age-related trends of treatment techniques and outcomes in patients treated for ruptured cerebral aneurysm in the United States. MATERIALS AND METHODS: Using the US Nationwide Inpatient Sample, we evaluated trends in treatment technique (clipping versus coiling) and discharge status of patients undergoing clipping or coiling of ruptured cerebral aneurysms between 2001 and 2009. Outcomes were evaluated in relation to 4 age strata: 1) younger than 50 years of age, 2) 50–64 years of age, 3) 65–79 years of age, and 4) patients 80 years or older. We compared outcomes between treatment groups for patients treated between 2001–2004 with those treated between 2005–2009. RESULTS: A significant increase in the proportion of patients undergoing endovascular coiling between 2001 and 2009 was noted for all age groups (P < .0001). For both clipped and coiled patients, mortality and the proportion of patients discharged to long-term facilities increased with age. Overall mortality for patients clipped and coiled decreased modestly for all age groups, and overall proportions of patients discharged home increased modestly (P < .01) for all age groups except those older than 80 years of age. CONCLUSIONS: Between 2001 and 2009, there has been a significant increase in the proportion of patients with ruptured aneurysms undergoing endovascular coiling rather than aneurysm clipping. This increase was more pronounced in older patients. Mortality from aneurysmal subarachnoid hemorrhage decreased during the past decade, regardless of aneurysm treatment technique.